THE COMPARATIVE ANALYSIS OF CORROSION SHIP PLATE 17QIF3563586 P15 IN PANJANG PORT AND BAKAUHENI PORT AT LAMPUNG - Oktarina, Kurniawati - (Jurnal Distilasi, 2019)
Low carbon steel is the main component that is widely used in the shipping industry for the manufacture of ship plate materials. The ship plate is a material that is used as a leather ship that is directly related to environmental factors. Environmental factors such as temperature, air salinity, wind and the others. The influence of environmental factore are ship's plate. The research of this study was conducted a variable factors that influence changes in pH so as to corrode vessel plate material in a period of time. The research method used was immersion of ship plate specimens for a period on three months. The sea water media of used in Panjang Port and Bahauhen Port at Lampung. The measurement variables for  specimens are temperature, pH, and corrosion and then calculated based on Faraday's law. The research of based on the results obtained that are temperature variable can be to influence pH. This is evidenced by the value a initial temperature of the immersion a specimens in Panjang Port seawater medium of 29,1oC which is a pH value of 8,7 and changes to 25,8oC with a pH value of 6. The same is true with the sea water media, with initial Initially a temperature value of 31,12oC for H 8.4 within three months changed to 25,8oC with a pH of 6,0. Meanwhile, the regression values obtained were 0,994 and 0,995 which is showed changes in pH in sea water increased the corrosion rate on the ship's plate. Keywords: Temperature, pH, Corrosion Rate, and Ship Plate